Lithuania : Accounting and Auditing - World Bank (Washington, DC, 2013)
This assessment of accounting and auditing standards and practices in Lithuania was focuses on the strengths and weaknesses of the institutional arrangements needed to observe International Accounting Standards (IAS) and International Standards on Auditing (ISA). Financial reporting and accounting by Lithuanian enterprises are currently governed by laws and other regulations issued in 1992 and 1993. New laws that came into effect in 2002 will significantly increase conformity between Lithuanian requirements and European Union (EU) Directives, establish a new national standard-setting body, and require greater compliance with IAS. There is a risk, therefore, that banks may be unable to fully comply with IAS because of conflicting requirements under national bank (BOL) regulations. While the quality of many of the IAS financial statements reviewed was good, there were a number of possible conflicts resulting from the application of BOL regulations and other circumstances peculiar to Lithuania. There is currently no enforcement or monitoring of compliance with IAS or national standards. The audit of financial statements must be carried out by qualified auditors and in accordance with Lithuanian standards that are based on ISA. While many audit firms make strenuous efforts to carry out audits in accordance with ISA, there are variations in the quality of audits. Furthermore, the quality of some audits is affected by management attitudes and misconceptions about the role of audits. Some of the powers granted to the Ministry of Finance for the supervision. of auditors have not yet been implemented. The implementation of these powers plus further changes are required in order to achieve conformity with EU Directives and greater use of ISA. The report makes a number of policy recommendations that are designed to achieve greater conformity between Lithuanian law and European Union Directives, and improve compliance with IAS and ISA.